2022
DOI: 10.4236/ojoph.2022.121003
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction Related to Their Eye Health Examination at Lúrio University Clinic in Nampula, Mozambique during COVID-19

Abstract: Introduction: Patient satisfaction is defined as the extent of agreement between what a patient expects to receive from his or her health experience and the perception of the level of care he or she actually receive. With the COVID-19 pandemic, many practices have to adapt to provide health ensuring patients' safety in first instance. Eye care procedures may be delayed during the pandemic, so eye safety is more important than ever, and it doesn't only focus on the examination room, all the clinic compartments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…On the other hand, studies were carried out in the country to assess user satisfaction with outpatient health services; 15 satisfaction with family planning services; 16 satisfaction with care during childbirth; 5 satisfaction regarding the eye health examination. 4 However, our findings are the first to show an introspection in which the assessment is carried out by the employees themselves as users of occupational health services.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…On the other hand, studies were carried out in the country to assess user satisfaction with outpatient health services; 15 satisfaction with family planning services; 16 satisfaction with care during childbirth; 5 satisfaction regarding the eye health examination. 4 However, our findings are the first to show an introspection in which the assessment is carried out by the employees themselves as users of occupational health services.…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, other studies reported low satisfaction values of prevalence of user satisfaction in Nampula province. 4 The low satisfaction value in Nampula may be due to several factors, such as the evaluation of a single service provided, the location of the health services and the period in which the study took place was during the period of the COVID-19 pandemic, a time when that service was restricted from health units. 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study involved 553 patients who attended ophthalmology clinics during the time of data collection, and most of them (76.5%, n = 423) were between the ages of 18 and 35, which is like Khathlan's retrospective descriptive study in Saudi Arabia [ 18 ], which found that the majority of patients who visited the ophthalmology clinics in 2018 were between the ages of 21 and 40. Also, Bambamba et al [ 19 ] conducted research to assess patient satisfaction with ophthalmology clinics in Mozambique, and they reported that 66.5% of their study sample was in the age group of 20-40 years old. This issue should be examined in further research to detect the common reasons for the increased frequency of ophthalmology clinic visits among young adults in comparison to the other age groups.…”
Section: Discussionmentioning
confidence: 99%